2020
DOI: 10.1101/2020.07.22.215954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

G-CSF Secreted by Epigenetically Reprogrammed Mutant IDH1 Glioma Stem Cells Reverses the Myeloid Cells’-Mediated Immunosuppressive Tumor Microenvironment

Abstract: Mutation in isocitrate dehydrogenase (mIDH) is a gain of function mutation resulting in the production of the oncometabolite, R-2-hydroxyglutarate, that inhibits DNA and histone demethylases. The resultant hypermethylation phenotype reprograms the glioma cells’ transcriptome and elicits profound effects on glioma immunity. We report that in mouse models and human gliomas, mIDH1 in the context of ATRX and TP53 inactivation results in global expansion of the granulocytic myeloid cells’ compartment. Single-cell R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 94 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…Myeloid cells are the most frequent immune cell type in the glioma TME, accounting for ∼60% of all glioma infiltrating immune cells. In GBM, myeloid-derived suppressor cells (MDSCs) are major immunosuppressive cells that hamper glioma immune response ( Kamran et al, 2017 ; Alghamri et al, 2020 ). Clinically, the frequency of MDSCs is associated with an unfavorable prognosis in glioma ( Rahbar et al, 2016 ).…”
Section: Glioma Tumor Microenvironmentmentioning
confidence: 99%
“…Myeloid cells are the most frequent immune cell type in the glioma TME, accounting for ∼60% of all glioma infiltrating immune cells. In GBM, myeloid-derived suppressor cells (MDSCs) are major immunosuppressive cells that hamper glioma immune response ( Kamran et al, 2017 ; Alghamri et al, 2020 ). Clinically, the frequency of MDSCs is associated with an unfavorable prognosis in glioma ( Rahbar et al, 2016 ).…”
Section: Glioma Tumor Microenvironmentmentioning
confidence: 99%
“…Myeloid-derived suppressor cells (MDSC) are a type of immature myeloid cells that are known to have immunosuppressive functions via different mechanisms that ultimately inhibit T cell functions (9,11,13). These cells have been found in the blood of glioma patients and in the tumor mass, and they have also been characterized in animal models (9,15,89,90) (91). It has been observed that the quantity and activation status of MDSC inversely correlates with patient survival and that they can be a predictor of WHO tumor grade (90).…”
Section: Immune Microenvironment In Brain Tumors: General Conceptsmentioning
confidence: 99%
“…Also, and in correlation to what Luoto et al found, mIDH1 gliomas tend to have less macrophages than wt-IDH1 tumors ( 97 ). Moreover, in an animal model of mIDH1 glioma in the context of ATRX and TP53 mutations, it has been observed that the presence of this mutation reprograms the tumor cell transcriptome, which affects not only immune cell infiltration but also the bone marrow differentiation of the granulocytic lineage ( 15 ). This effect was found to be mediated by G-CSF secretion by mIDH1 glioma cells, which prompted the expansion of pre-neutrophils, while reducing the immunosuppressive phenotype of the granulocytes encountered in mIDH1 tumors’ TME ( 15 ).…”
Section: Glioma Immune Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations